2014
DOI: 10.1002/pd.4432
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of angiogenic factors to maternal and neonatal manifestations of early‐onset and late‐onset preeclampsia

Abstract: Angiogenic imbalance is more pronounced in patients with early-onset preeclampsia and correlates with worse clinical outcomes, especially for the neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 57 publications
(127 reference statements)
8
28
0
Order By: Relevance
“…Although both of these lesions are generally considered to reflect activation of the innate immune response (macrophages), there is accumulating evidence suggesting participation of the adaptive limb of the immune response as well [129145]. Specifically, T lymphocytes have been detected in the early stages of atheroma formation and they persist as the lesions grow and eventually rupture [146].…”
Section: Discussionmentioning
confidence: 99%
“…Although both of these lesions are generally considered to reflect activation of the innate immune response (macrophages), there is accumulating evidence suggesting participation of the adaptive limb of the immune response as well [129145]. Specifically, T lymphocytes have been detected in the early stages of atheroma formation and they persist as the lesions grow and eventually rupture [146].…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that the studies cited are generally based on the ‘old’ classification of preeclampsia with the requirement for proteinuria. Preeclampsia is also distinguished as early onset vs late onset preeclampsia (Moore and Redman, 1983; Paruk and Moodley, 2000) based on evidence that the two entities have distinct pathophysiologic underpinnings (Nelson et al, 2014; Pinheiro et al, 2014) Investigators have most often classified early-onset and late-onset disease as preeclampsia that prompts delivery <34 weeks or ≥34 weeks gestation, respectively.…”
Section: Complement and Hypertensive Disorders Of Pregnancymentioning
confidence: 99%
“…On the other hand, PE is a heterogeneous disorder, and it has been suggested that early-(EO) and late-onset (LO) PE could have differing physiopathological pathways [8,9], which is why evaluating the mechanism previously described, while considering this classification, is a matter of interest.…”
Section: Introductionmentioning
confidence: 99%